Infra-Red Therapy Reduces Lower Extremity Pain in Elderly with Osteoarthritis - I Gede Yudiana Putra; Ni Made Sri Muryani; Putu Intan Daryaswanti (Faculty of Nursing, Universitas Jember, 2021)
Background: Elderly is someone who because of his advanced age experiences biological, physical, psychological and social changes. One of the physical changes that occur in the elderly is a problem with decreased area of ​​motion, one of which is osteoarthritis which often affects several joints, such as the joints of the fingertips, thumbs, knees, hips, heels and causes joint pain. Pain is very disturbing and makes it difficult for the elderly to do their activities, so the need for proper treatment is to reduce the pain that occurs due to osteoarthritis. One therapy that can be recommended is non-pharmacological therapy, namely infrared therapy. Purpose: This study aims to determine the effect of infrared therapy on the reduction of lower limb pain in the elderly with osteoarthritis. Methods: The design of this study is a quasy experimental design with a pre-post-test control group design .. where the elderly will be divided into 2 groups, namely the treatment group given infrared therapy and the control group who did not receive infrared therapy. This research was conducted at PSTW Wana Sraya Denpasar, for three weeks from July 20 to August 2020. The sample in this study was 30 elderly who experienced pain in their lower extremities with osteoarthritis. Results: The results of this study showed that most of the elderly> 65 years were 63.3% and 66.6% female. The elderly mostly experience pain scale 4-6 (moderate pain) in the lower extremities. The results of statistical tests showed that giving infrared therapy had an effect on reducing the pain scale in the lower extremities in the elderly with OA (p = 0.000) Conclusion: There was a decrease in the pain scale before and after infra-red administration and there was a significant effect on reducing lower limb pain in the elderly with osteoarthritis who were given infrared 8 times a week for 3 weeks.